World Image in Yassavi’s Wisdoms - Muyassar Ibrohimova (Genius Publishing Group, 2022)
The article discusses the importance of the image of the world and the skill of artistic imagery in the Khoja Ahmad Yassavi’s wisdoms. Moreover, in the article is explained with examples that the role of the world’s image in the literary activity of the poet, connection between Islamic holy books and poems of Yassavi.
Keywords: Wisdom; Jifa; World Life; Dervish